Rekonseptualisasi Shura dalam Sistem Konstitusional Modern: Analisis Tafsir Tematik - Muh Tabran; Rosmini; Hasyim Haddade (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2026)
The phenomenon of super-majority coalitions, coupled with strict factional discipline and the low scientific competence of some legislators, has altered the essence of deliberation. Consequently, there is a risk that the majority will make decisions that disregard public aspirations. This study aims to analyze the impact of suboptimal deliberation and decision-making, examine Qur’anic verses regarding sound decision-making practices, and propose improvements to foster healthy meeting ethics within the people’s representative body. The method used is a qualitative literature review that integrates thematic exegesis to analyze Qur’anic verses in order to assess the actual conditions in the Indonesian parliament. Verses such as Surah Al-Shura verse 38, Surah Al-Baqarah verse 233, and Surah Ali Imran verse 159 were collected and analyzed in depth to identify the fundamental criteria for ideal deliberation. The research results formulated four main criteria. First, the need for standard limits on scholarly competence. Second, the existence of equal rights for all meeting participants. Third, the freedom of expression for every council member to defend the interests of the people. Fourth, the achievement of consensus must be based on mutual consent. The study’s conclusions offer new insights for the development of Islamic Constitutional Law by establishing Qur’anic values as a fundamental guide in restructuring the country’s representative institutions